California History (JSTOR)
Published since 1922, California History contains scholarly, illustrated essays focusing on California and the West from pre-Columbian to recent times. The quarterly journal also features California Historical Society collection highlights, pictorial essays, book reviews, a full-page photographic feature, and an editor's column. California History is committed to publishing new or under-explored subjects, innovative approaches, and challenging interpretations. Images and graphic elements are considered essential content. Articles in California History are based on solid research and critical thinking and connect California to the region, nation, and world. Among the earmarks that particularly distinguish submissions are California subjects with broad appeal; results of new research utilizing hitherto unknown sources; presentation schemes that provide alternative viewpoints, revisionist hypotheses, and innovative explanations; and treatments that relate historical events to issues of contemporary relevance and future concern. In short, California History seeks to be as innovative as the state it presents.
Keywords: American Studies